Association of serum biochemical parameters with growth performance and gut microbiota in large white pigs - Liang, Shuang; Zhang, Yanping; Xia, Qin; Liu, Xiaoxiao; Liang, Jing (Frontiers in Veterinary Science, 2026)
BackgroundSerum biochemical parameters are crucial indicators of animal health and metabolism, providing valuable insights into nutritional and physiological status.MethodsTo investigate the correlations among serum biochemical indicators, growth traits, and gut microbiota, a total of 274 Large White pigs (124 boars and 150 sows) were selected as experimental subjects in this study. At the early fattening stage (80 days of age), blood samples and fecal samples were collected from all pigs. Five key serum biochemical parameters (Glu, LDH, HDL-C, LDL-C, sCr) and fecal microbial diversity were measured. Additionally, the main economic traits of the pigs were measured following the standard evaluation criteria for swine production performance.Results and discussionResults showed that serum creatinine (sCr) was negatively correlated with residual feed intake (RFI), average daily feed intake (ADFI), feed conversion ratio (FCR), and backfat thickness (r = −0.13 to −0.25, p < 0.05), but positively correlated with loin muscle area (r = 0.13, p < 0.05). Lactate dehydrogenase (LDH) was negatively correlated with FCR (r = −0.24, p < 0.05) and RFI (r = −0.26, p < 0.05). At the genus level, LDH was positively correlated with Prevotella, Faecalibacterium, Roseburia, and Desulfovibrio, and negatively correlated with Fibrobacter. Meanwhile, sCr showed positive correlations with Treponema and CF231, and negative correlations with Subdoligranulum, Eubacterium, and Dorea. These genera may serve as microbial biomarkers for sCr and LDH levels. Our findings provide valuable insights for early-stage breeding selection and further research into blood biochemical indicators in pigs.